Agarwal Packers and Movers Limited - Roy, Debjit, (SAGE Knowledge. Cases., 2015)
Agarwal Packers and Movers Limited (APML) is a leading logistics and solution provider for household goods relocation who in past was facing problems due to increasing number of customer complaints and claims and increasing packaging costs. An apparent solution to these problems was increasing freight cost. However, APML decided not to choose this easy way, as it was in contrast to the company's philosophy to provide superior services at lowest prices. Mr. Ramesh Agarwal, Chairman cum Managing Worker of APML and his entire team was committed to overcome these problems keeping in line with the company's core values. Hence, solutions were offered by modifying the processes and innovating the services in such a way that it resulted in customer's delight. This was because the prices were not increased though most of the customer problems were resolved. In addition, each and every innovation at APML was viewed with the objective to fulfill its Corporate Social Responsibility (CSR). For instance, introduction of LED boxes not only resolved the customer complaints, but also, resulted in reduced cost and saving 160 trees per year. APML, as an organization, had a very strong customer-centric approach. Simultaneously, it also valued its employees, who it believed were its biggest strength. It was evident from its policy to share the earnings with the employees. Reward and recognition, to boost up employee morale was a regular process at APML. The company was also committed towards Employee Health and Safety (EHS) measures. Now APML's focus was on sustaining the innovative ideas as well as keeping the team motivated to think 'out of the box' in future as well.